Accumulation of nutrients during the formation of star fruit cultivars under different irrigation regimes - Rozane, Danilo Eduardo; Prado, Renato de Mello; Paula, Betania Vahl de; Santos, Eduardo Maciel Haitzmann dos; Natale, William; Amorim, Daniel Angelucci de; Hernandes, Amanda (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2022)
Nutrient accumulation during the formation of star fruit (Averrhoa carambola) trees can be affected by the water regime and by the cultivar, but the details are not yet known for this species. The aim of this study was to evaluate the nutrient uptake of two star fruit cultivars in the formation phase under two irrigation regimes. The experiment was developed with a completely randomized design, with subdivided plots, with two irrigation levels (with and without irrigation) as plots, and two star fruit cultivars as subplots ('B-10' and 'Golden Star') and seven collection times from 0 to 720 days after transplanting (DAT) into the field as sub-subplots with six replicates. Nutrient uptake was evaluated in stem and leaves, and it was possible to observe that nutrient uptake and the average accumulation rate followed the dry matter mass accumulation of star fruit trees in formation. Nutrient uptake by shoots at 720 DAT differed for the Golden Star cultivar in the rainfed regime and for the B-10 cultivar in both irrigation regimes. There was no difference and followed the sequence Ca > K > N > Mg > S > P > Mn > Fe > Zn > B > Cu, and for Golden Star cultivar in the irrigated regime, the accumulation sequence was Ca> K> N> Mg> Mn> P> S> Fe> Zn > B> Cu. The highest accumulation occurred in the irrigated regime regardless of cultivar. Golden Star cultivar accumulated, on average, larger amounts of N, P, K, Mg, S, Fe and Mn.